Histological investigation of the protective effect of metformin on testis and sperm parameters in obese rats with type 2 diabetes mellitus - Budak, Özcan (Journal of Surgery and Medicine, 2021)
Background/Aim: Diabetes mellitus (DM) is thought to have adverse effects on the male reproductive system. Metformin (MTF) is a widely used drug in the treatment of DM. This study hypothesized that MTF can reduce the harmful effects of DM on the male reproductive system in addition to diabetes treatment. Methods: Twenty-one adult (15-18 g, 11-12 months) C57BL6 male mice were randomly assigned to three groups, as follows: The Control group (C), Diabetes group (D), and Diabetes + Metformin (D+MTF) treatment group. Groups D and D+MTF were fed a diet composed of 60% fat for four weeks. DM was created by administering a single dose of 30 mg/kg streptozotocin intraperitoneally (i.p.). MTF was given through gavage at a dose of 300 mg/kg/day. At the end of the experiment, sperm parameters were evaluated in the testicular tissue. Histomorphology features and immune expressions of VEGF, Caspase-3, and Ki-67 were evaluated in testicular tissue sections stained with Hematoxylin and Eosin (HE). Results: Sperm concentration, motility, and morphological characteristics of diabetic mice were significantly reduced compared to control, and MTF-treated mice. Seminiferous tubule diameters and Johnsen scores were significantly higher in the control and D+MTF groups when compared to the diabetic group. VEGF and Ki-67 immune expression were significantly higher in the control and D+MTF groups compared to the D group (P=0.001, and P=0.002, respectively). Because of D, Caspase-3 positive cell density was higher in the D group compared to the control and D+MTF groups (P=0.002). Conclusion: Diabetes mellitus had adverse effects on sperm parameters and the testicular tissue. High glucose levels with decreased VEGF immune expression damaged spermatogenic cells and decreased proliferation and differentiation due to impaired intratesticular vascularity. MTF treatment reduced the damage in spermatogenic cells and contributed to the differentiation and division of cells through the restoration of vascularization.